Numerical Simulation of Ice Crystal Supercooled Droplet Mixed Phase Icing Based on the Improved Messinger Model - Zhengzhi Wang; Wei Zhong; Chunfu Liu; Huanyu Zhao; Senyun Liu (International Journal of Aerospace Engineering)
The ice crystal supercooled droplet mixed phase icing problem is an important research direction in aircraft icing and has received more attention in recent years. The thermodynamic process of the water film after the ice crystals impact on the surface determines the final ice shape, which is an important part of the accurate prediction of aircraft icing. In this paper, a thermodynamic model of ice crystal supercooled droplet mixed phase icing is proposed based on the extended Messinger model, according to the results of flow field and particle trajectory calculations. In this model, the mass and energy conservation equations of ice crystals, supercooled droplets, and liquid water are considered. The equations take the process of ice crystal adhesion and erosion into account, and the solution method of the equations is given. Ice shapes are calculated under various ice crystal supercooled droplet mixed phase conditions and compared with experimental results to demonstrate the validity of the numerical method. The effects of ice crystal erosion rate, melting ratio, and adhesion coefficient on the calculation results are analyzed by a numerical method. The results show that the ice crystal erosion rate has little effect on the ice shape, while a larger melting ratio and adhesion coefficient lead to more ice accretion.